Sympathetic nervous system activity and unattended blood pressure measurement. (3rd October 2022) - Manta, E; Andrikou, I; Dimitriadis, K; Drogkaris, S; Siafi, E; Filippou, C; Tatakis, F; Thomopoulos, C; Konstantinidis, D; Tsioufis, K
Abstract: Background/Introduction: Sympathetic nervous system activation plays a crucial role in the pathophysiology and variability of hypertension. It has been hypothesized that measurement of unattended blood pressure (BP) may provide additional information to conventionally attended BP measurement, as it can lead to the limitation of the white coat effect. Purpose: The aim of this study was to demonstrate the relationship of sympathetic nervous system activation and BP measurement variations with and without medical supervision. Methods: We studied 103 untreated hypertensive patients, who underwent muscle sympathetic nerve activity (MSNA) estimation by microneurography. Both unattended (patient alone in the room, an oscillometric device programmed to perform 3 BP measurements at 1-minute intervals, after 5 minutes of rest) and attended BP measurements were conducted in all participants, with the same device, on the same day of MSNA recording in random order. Patients were divided into two groups based on the difference between attended and unattended BP. In group A, patients had unattended BP greater than attended BP (n=31) and in group B, patients had unattended BP lower than attended BP (n=72). The two groups were compared regarding the median value of MSNA recordings in our population (median MSNA = 63 bursts per 100 heartbeats). Results: The two groups did not differ as regards both attended SBP levels (group A: 142.3±15.4 mmHg, group B: 145.6±13.7 mmHg, p=0.29) and attended DBP levels (group A: 89.2±9.8 mmHg, group B: 91.2±11.5 mmHg, p=0.25). A difference was observed concerning unattended SBP levels (group A: 152±16.3 mmHg, group B: 142.5±13.8 mmHg, p=0.03) and unattended DBP levels (group A: 94.4±10.3 mmHg, group B: 85.2±11.8 mmHg, p<0.01). Higher levels of MSNA were recorded in patients in group A when compared to group B, although this difference was not statistically significant (66.8±15.6 vs. 61.6±14.8 bursts per 100 heartbeats, p=0.11). Higher percentage of patients in group A had MSNA levels greater than the median value of MSNA compared to group B (68% vs 46% respectively). Conclusions: In the present study, we found that the majority of patients who exhibit higher BP during the unattended measurement also record high MSNA values, suggesting a more stimulated sympathetic nervous system. On the contrary, most of the patients who can calm down during the unattended measurement exhibit lower levels of MSNA. More patients are needed to fully determine the clinical significance of this observation. Funding Acknowledgement: Type of funding sources: None.